2013 IEEE 15th International Workshop on Multimedia Signal Processing (MMSP) 2013
DOI: 10.1109/mmsp.2013.6659305
|View full text |Cite
|
Sign up to set email alerts
|

Automatic extraction of pinna edges for binaural audio customization

Abstract: The contribution of the external ear to the headrelated transfer function (HRTF) heavily depends on the listener's unique anthropometry. In particular, the shape of the most prominent contours of the pinna defines the frequency location of the HRTF spectral notches along the elevation of the sound source. This paper addresses the issue of automatically estimating the location of pinna edges starting from a set of pictures produced by a multi-flash imaging device. A basic image processing algorithm designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…where c is the speed of sound and approximated as fifth-order polynomial functions of the elevation angle F n i , i ϭ 1, 2, 3. The effectiveness of the multi-flash device in extracting pinna contours has been investigated in a previous work (Spagnol et al, 2013b). Results on 30 subjects revealed that the ear canal point is always correctly identified and that 93.3 per cent of the edge tracks are correctly extracted.…”
Section: Synthetic Individual Binaural Audio Deliverymentioning
confidence: 98%
“…where c is the speed of sound and approximated as fifth-order polynomial functions of the elevation angle F n i , i ϭ 1, 2, 3. The effectiveness of the multi-flash device in extracting pinna contours has been investigated in a previous work (Spagnol et al, 2013b). Results on 30 subjects revealed that the ear canal point is always correctly identified and that 93.3 per cent of the edge tracks are correctly extracted.…”
Section: Synthetic Individual Binaural Audio Deliverymentioning
confidence: 98%
“…INDIVIDUALIZATION OF NON-INDIVIDUALIZED BINAURAL SYNTHESIS USING FRONTAL PROJECTION HEADPHONESICA[203,210,211]. The individual weights are derived from the anthropometric parameters that are captured by optical descriptors either by directly measuring, or derived from pictures, or by obtaining a 3D mesh of the morphology[42,212].The solution to the problem of diffraction of an acoustic wave with the listener's body results in individual HRTFs. This solution may be obtained by analytical or numerical methods, such as the boundary element method (BEM) or the fi nite element method (FEM) [42,188].…”
mentioning
confidence: 99%